Dual-targeted carbon-dot-drugs nanoassemblies for modulating Alzheimer's related amyloid-β aggregation and inhibiting fungal infection. (September 2021) - Yan, Chaoren; Wang, Chaoli; Shao, Xu; Shu, Qi; Hu, Xiaoling; Guan, Ping; Teng, Yonggang; Cheng, Yuan
Abstract: Amyloid aggregation and fungal infection, especially amyloid beta (A β ) peptide and Candida albicans are considered as two of the crucial pathogenic agents in Alzheimer's disease (AD). In this work, we propose an innovative treatment strategy for AD, targeting at not only A β aggregation but also Candida albicans infection. Here, a high-performance nanomaterial, namely gCDs-E, have been prepared by self-assembled of glycosylated carbon dots (gCDs) and epigallocatechin-3-gallate (EGCG). Surprisingly, gCDs-E can not only suppress the fibrillation of A β and disaggregate A β fibrils, but also effectively inhibit the activity of Candida albicans . More importantly, the prepared gCDs-E can effectively cut down the cytotoxicity of amyloid aggregations, and the cell viability reached to 99.2%. In addition, the capability of the gCDs-E for blood brain barrier (BBB) penetration was also observed using a normal mice model. Above all, the gCDs-E greatly cleaned A β deposition and improved memory impairment in APP/PS1 transgenic AD model mice, confirming its potential as therapeutic agent for AD treatment. Graphical abstract: Image 1